ASSESSING GROUNDWATER POTENTIAL USE FOR EXPANDING IRRIGATION IN THE BURITI VERMELHO WATERSHED - Wendt, Doris Elise; Rodrigues, Lineu Neiva; Dijksma, Roel; C Van Dam, Jos (IRRIGA, 2015)
ASSESSING GROUNDWATER POTENTIAL USE FOR EXPANDING IRRIGATION IN THE BURITI VERMELHO WATERSHED DORIS ELISE WENDT1; LINEU NEIVA RODRIGUES2; ROEL DIJKSMA3; JOS C VAN DAM4 [1] Wageningen University, the Netherlands. doris.de.wendt@gmail.com; 2Embrapa Cerrados, BR020, km18, CEP 73310970, Planaltina, DF. lineu.rodrigues@embrapa.br; 3 Hydrology and Quantative Water Management Group, Wageningen University, the Netherlands. roel.dijksma@wur.nl; 4 Soil Physics and Land Management Group, Wageningen University, the Netherlands. jos.vandam@wur.nl; 1 ABSTRACT In Brazil, the increasing middle class has raised food demand substantially. The Brazilian Savannah (Cerrados) is one of the rare places where agriculture can expand and address this new demand without jeopardizing the environment. Cerrados has a strictly divided dry and wet season. The dry season lasts from May to September. This long period contributes to various problems such as water shortages, conflicts and insecure food production. Without irrigation, only two crops can be grown per year in this region. Production suffers with a recurrent drought. Because agricultural production is uncertain, irrigation has an important role in this context, but its expansion is limited by water availability. Water conflicts have already occurred in some watersheds, which may jeopardize agriculture and decrease the livelihood of rural communities. In general, water for irrigation is limited to surface water. Therefore, it is important to investigate alternative sources of water, like groundwater. The purpose of this study is to assess the groundwater potential for expanding the irrigated area in a small-scale catchment (Buriti Vermelho, DF, Brazil). The current water demand was investigated and simulated by an Irrigation Strategies Simulation Model (MSEI). A daily water balance was computed, which quantified catchment storage over time. In addition, groundwater behavior and availability were investigated by recession curve analysis. The irrigated area was changed using two scenarios that showed different effects in both catchment surface water balance and groundwater levels. A decline in groundwater levels is seen in all scenarios one year after the beginning of extra extraction. With time, water levels may decline beyond the natural recovery capacity, which will certainly penalize poorer farmers and result in areas being taken out of agricultural production. Keywords: Base flow Recession, Catchment Hydrology, Hydrogeology, Crop Water Productivity WENDT, D.E.; RODRIGUES, L.N.; DIJKSMA, R.; DAM, J.C. VAN AVALIAÇÃO DO POTENCIAL DE USO DA ÁGUA SUBTERRÂNEA PARA EXPANSÃO DA IRRIGAÇÃO NA BACIA DO BURITI VERMELHO 2 RESUMO A demanda por alimentos no Brasil cresceu substancialmente devido, entre outras coisas, ao aumento da classe média. O Cerrado brasileiro é um dos poucos lugares no país onde a agricultura ainda pode expandir e atender a essa nova demanda, sem comprometer o meio ambiente. A região do Cerrado possui duas estações climáticas bem definidas, uma seca e outra chuvosa. O longo período da estação seca, que vai de maio a setembro, contribui para o surgimento de vários problemas, entre eles restrições hídricas, conflitos e insegurança na produção de alimentos. Sem irrigação, apenas dois plantios podem ser feitos por ano. Os cultivos sofrem com os veranicos e a produção é incerta. A irrigação é de fundamental importância nesse contexto, mas sua expansão é limitada pela disponibilidade de água. Em algumas bacias hidrográficas já se observam a ocorrência de conflitos, que podem comprometer a agricultura irrigada e a qualidade de vida das comunidades rurais. De maneira geral, a água para irrigação é de superfície. Desta forma, é importante investigar fontes alternativas de água, com vista ao crescimento da irrigação, tais como a água subterrânea. O Objetivo deste trabalho é avaliar a viabilidade de se utilizar água subterrânea para expandir a agricultura irrigada na bacia hidrográfica do Buriti Vermelho, DF, Brasil. A demanda atual de água foi estimada por meio de um modelo de simulação de estratégias de irrigação (MSEI). Um balanço diário da água no solo foi realizado. O comportamento e a disponibilidade de água subterrânea foram avaliados por meio de uma análise da curva de recessão. Para fins da análise, foram utilizados três cenários de área irrigada, que indicaram diferentes efeitos tanto no perfil do balanço de água no solo quanto no nível do lençol freático. Nos três cenários avaliados, em apenas um ano após a expansão da área irrigada, verificou-se um rebaixamento do lençol freático, que pode atingir níveis abaixo da sua capacidade natural de recuperação. Esse rebaixamento penalizará principalmente os agricultores menores. Em alguns casos haverá necessidade de interromper a produção em algumas áreas. Palavras-chave: Curva de recessão, hidrologia, hidrogeologia, produtividade do uso da água